PENGARUH PENGGUNAAN GAME EDUKASI BERBASIS AUGMENTED REALITY TERHADAP KEMAMPUAN MENYIMAK CERITA SISWA KELAS III SDN 255 PARANGLOHE KABUPATEN BULUKUMBA - Karnilawati; Ratnawati; Desy Ayu Andhira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using an Augmented Reality-based educational game on the listening skills of third-grade students at SDN 255 Paranglohe, Bulukumba Regency. This study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest design. The subjects were 10 third-grade students. Data collection used a story listening test administered before and after the application of Augmented Reality media in the learning process. The results showed that students' listening skills improved after using the media. The average score for students in the pretest was 55.00, increasing to 84.00 in the posttest. These results indicate that the use of an Augmented Reality-based educational game significantly improved students' listening skills. The use of this technology helps students focus better and visualize the story content more easily through direct interaction with digital objects. Therefore, Augmented Reality-based educational games can be used as an effective alternative learning medium to improve elementary school students' listening skills.